Diagnostic dilemma in Kaposi’s sarcoma - Rao B.S Satish; Tauro F Leo; Menezes Theobald Leo; B Nandakishore; K Praveen Kumar (Indian Journal of Plastic Surgery)
Kaposi′s sarcoma is described as cutaneous and extracutaneous neoplasm predominantly affecting older individuals. Though earlier uncommon and endemic to certain African areas, its incidence is on a rise due to infections with human immunodeficiency virus and also due to transplant-associated immunosuppression. Further, certain benign conditions like Pseudo Kaposi′s sarcoma, certain infective conditions like bacillary angiomatosis of acquired immunodeficiency syndrome can mimic Kaposi′s sarcoma both clinically and histologically leading to a diagnostic dilemma. We report such a case here.